Morphology and ultrastructure of the infrabuccal pocket in Strumigenys ants. (May 2022) - Wang, Chu; Cocco, Alessio; Lin, Chung-Chi; Billen, Johan
Abstract: The morphology of the infrabuccal pocket has been studied with light and electron microscopy (SEM, TEM) in 19 species of Strumigenys ants. The structural organization is similar in workers, queens and males, and supports the involvement of the pocket in the filtration of food particles before they can enter the digestive tract. A carpet of posteriorly oriented bristle hairs on the hypopharynx first guide ingested food into the pocket, where large solid particles are compacted into a pellet that will be regurgitated. The remaining products enter the digestive tract through a filtering wall of parallel hair combs lining the pharynx interior that are directed against the food flow. This mechanical filtering allows only liquids and sufficiently small food particles to enter the digestive system. The wall of the infrabuccal pocket is differentiated into a conspicuous glandular epithelium, of which the ultrastructural characteristics can be understood as an adaptation against the frequent shape changes of the pocket. The gland elaborates a non-proteinaceous secretion, although its functional significance still remains unknown. Graphical abstract: Image 1 Highlights: We studied the infrabuccal pocket (IBP) in 19 species of Strumigenys ants. The IBP assists in filtering food particles before they pass into the digestive tube. The structural organization of the IBP is similar in workers, queens and males. The wall of the IBP is differentiated into a glandular epithelium. The function of the IBP-gland remains unknown.